ESTIMATION OF POSTOPERATIVE PAIN SYNDROME AT THE HERNIOPLASTY - D. V. Turkin (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The article reviews the problem of course of postoperative period, in patients operated on account of different kinds of inguinal hernias. Age and. gender of patients, kind of hernioplasty, anatomic peculiarities of inguinal hernias were the factors determining intensity and continuance of postoperative pain syndrome. 239 patients had operations during 2007—2011 years. The pain was evaluated by the subjective 10-points scale on the 1st and the 3rd day of postoperative period. Retrospective analysis was used. The aim. of the research was to determine the most significant factors in development of postoperative pain syndrome. Data of retrospective analysis showed that the age of patients is independent prognostic factor that determines pain syndrome in postoperative period at the inguinal hernias, but the gender, anatomic characteristics and surgical technique (not the type of operation) don't influence pain syndrome. Thus the age of patients should be taken into consideration at the prescription of analgetics in postoperative period.